Reduction of gastro-intestinal adverse effect risk in long-term therapy with acetylsalicylic acid - E. Yu. Bulakhova; O. Yu. Korennova; V. A. Kozyreva; S. D. Kurochkina; S. A. Murotova (Кардиоваскулярная терапия и профилактика, 2010)
Aim. To study the safety and tolerability of long-term anti-aggregant therapy in patients with coronary heart disease (CHD), comparing enteric-coated acetylsalicylic acid (ASA) and standard ASA forms. Material and methods. The study included 100 CHD patients, with myocardial infarction in anamnesis. All participants received ASA and were retrospectively divided into two groups: Group I (n=50) received entericcoated ASA (Aspirin Cardio 100 mg/d) for two years; Group II (n=50) received standard ASA (125 mg/d) for two years. The incidence of dyspeptic symptoms and gastro-duodenal ulcers and erosions was assessed. Gastric and duodenal endoscopy was performed at baseline, as well as 6, 12 and 24 months later. Results. Long-term Aspirin Cardio therapy, according to endoscopy data, was less frequently associated with gastro-duodenal ulcers and erosions, or dyspeptic symptoms, than the treatment with standard ASA. Conclusion. The results obtained support better tolerability and safety of enteric-coated form of ASA, Aspirin Cardio.